A systematic review and meta‐analysis of Toxoplasma gondii in roe deer (Capreolus capreolus) and red deer (Cervus elaphus) in Europe. (8th November 2020) - Fanelli, Angela; Battisti, Elena; Zanet, Stefania; Trisciuoglio, Anna; Ferroglio, Ezio
Abstract: The objective of this systematic review and meta‐analysis was to summarize the available knowledge on the seroprevalence of T. gondii in roe deer ( Capreolus capreolus ) and red deer (Cervus elaphus) in Europe. A computerized literature search of electronic databases (PubMed and CAB abstracts) was performed along with hand searches of library resources for relevant papers, books, abstracts and conference proceedings. A random‐effect model was employed to calculate pooled seroprevalence estimates with 95% confidence intervals, and I 2 statistic was used to assess heterogeneity. Further, moderator analysis was performed to evaluate the effect of geographical area on the seroprevalence in roe deer. From a total of 190 studies initially identified, 16 and 8 articles were included for roe deer and red deer, respectively. These comprise 3, 913 roe deer and 2, 913 red deer from different European countries. The pooled seroprevalence was estimated to be 29% (95% CI: 23%–35%) in roe deer and 15% (95% CI: 10%–20%) in red deer. High heterogeneity was detected in the seroprevalence data within each species. In roe deer, the pooled seroprevalence estimate was significantly different according to geographical area with 40% (95% CI: 31%–49%) in Western Europe, 31% (95% CI: 21%–43%) in Northern Europe, 27% (95% CI: 15%–41%) in Eastern Europe and 21% (95% CI: 14%–28%) in Southern Europe. The present study indicates a moderate exposure to T. gondii in roe deer and red deer in Europe, with very high prevalence in Western Europe. Our results highlight the significant risk associated to the consumption of venison, encouraging proper handling and cooking of game meat to prevent toxoplasmosis in humans.